Influence of oriented control of the ball with the sole of the foot in children's futsal/Influencia del control orientado del balón con la planta del pie en el futsal infantil - Alexander Castro Figueredo; Esteban Juan Pérez Hernández; Héctor Noa Cuadro (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
The research began with children 10-12 years of age from the "Pueblo Nuevo" sports complex in the municipality of Holguín. It had as the objective: to demonstrate the influence that the oriented control technique of the ball with the sole of the foot has on Indoor football practitioners, a children's category of the Holguín "Pueblo Nuevo" team, to develop fast play. Theoretical and empirical methods and techniques were used; within the latter, observation, interview, survey and measurement were worked on, which allowed raising the scientific rigor of the elements analyzed and processed. The results obtained allowed to demonstrate why it is vitally important to use the oriented control technique of the ball with the sole of the foot during the game in the game of indoor football and, specifically, to develop it from an early age. The research, in addition, performs an analysis of this technique, taking into account the rules and game systems, based on the review and analysis of previous research, on direct observation in the training and games of the children's category of the sports team " Pueblo Nuevo ". " of the municipality of Holguin.